Persepsi Wisatawan Terhadap Objek Wisata di Kabupaten Aceh Tengah - Wahyudi, Wahyudi (Politeknik Pariwisata Medan, 2023)
Central Aceh Regency as one of the western most regions of Indonesia is one of the areas that is the choice of tourist destinations. The natural condition of Central Aceh district which is located in the highlands makes this area crowded with tourists. There are various types of tourism found in Central Aceh district ranging from nature tourism, agro tourism, and historical tourism. This study aims to determine the perception of tourists towards tourism objects in Central Aceh district in terms of Attraction, Amnesity, Accessibility and Hospitality Aspects. This study uses a quantitative descriptive research approach with primary data sources collected using a questionnaire via google form and limited interviews with several respondents. The results showed that the perception of tourists to tourism objects in Central Aceh Regency as a whole is quite good with a percentage of 78%. In particular, tourist perceptions of the attractions aspect of Central Aceh tourism objects are classified as good with a percentage of 85%, the amnesity aspect is quite good with a percentage of 72%, the accessibility aspect is quite good with a percentage of 71% and the hospitality aspect is classified as good with a percentage of 86%.